Department Of Psychiatry, BPKIHS And It’s Contribution To Mental Health Literature Of Nepal (Journal of Psychiatrists' Association of Nepal, 2014)
Mental health and Psychiatry are relatively new as a medical specialty in Nepal. Psychiatry and its issues are still the matter of stigma, mystery, ignorance and negligence not only in public but also in professional and policy-maker level. It is yet to receive its due space in health policy in terms of: program, priority and resource allocation. Despite of some achievements in mental health field (service, teaching and research), they are too far from satisfaction. Along with other responsibilities in this pretext, a department of psychiatry of a teaching institute naturally bears on its shoulder a huge burden of spreading scientific information, adding to literature and destigmatizing mental health issues. The fact, data, information and awareness is a main means of changing present situation. This article intends to briefly outline the milestones, major attempts, achievements and publications in this direction, of Department of Psychiatry of B.P. Koirala Institute of Health Sciences (BPKIHS), a prominent centre for the medical education, service and research in Nepal. The basis of this review are: Journals, Abstract-books, BPKIHS Annual Reports, Thesis, other research works, Internet search, books, papers and personal communication with both concerned faculty members and students coming into the knowledge of the author. DOI: http://dx.doi.org/10.3126/jpan.v3i1.11354 J Psychiatrists’ Association of Nepal Vol .3, No.1, 2014: 48-57